Pemberdayaan Masyarakat Desa Suka Galih Bojong Keji Kecamatan Mega Mendung Kabupaten Bogor: Sosialisasi Pembuatan Detergen Cair Dari Buah Lerak - Hidajat, Koerniawan; Lukiyana, Lukiyana; Ahmad, Masnia; Nathadiharja, Sri Sukartono; Diansyah, Diansyah (Jurnal Pemberdayaan Nusantara, 2025)
Environmental pollution in society is a serious impact that must be reduced and even eliminated. The use of natural ingredients is a solution to household waste, especially the use of liquid detergent soap chemicals. The purpose of community empowerment in Suka Galih Village Bojong Keji Megamendung District, Bogor Regency through the socialization of making lerak fruit liquid detergent is to provide added value to the business of increasing additional household income for the community in general and especially in RT.04 RW.03 Suka Galih Village. Compounds or substances in lerak fruit are able to reduce environmental pollution by not excessive use. The socialization of making lerak detergent soap was carried out on Monday, February 24, 2025 ± 09.00 am to 15.00 pm at Mr. Adam's house, Chairman of RT.04 RW.03 Suka Galih Bojong Keji Village. Socialization participants were ± 50 (fifty) PKK mothers of RT.04 RW.03 Suka Galih Bojong Keji Village. Socialization was carried out using a projector and direct practice. This direct socialization is expected that in the future the community will understand the making of detergents made from natural raw materials without chemicals.